Applications of Raman spectroscopy to urology - Hart Prieto, Maria Consuelo (Cranfield University, 2006)
Raman spectroscopy is an optical technique that can interrogate biological tissues. In doing so it gives us an understanding of the changes in the molecular structure that are associated with disease development. The Kerr gating technique uses a picosecond pulsed laser and fast temporal gating of inelastically (Raman) scattered light. The tissue samples used were taken following fully informed consent and ethics approval. Bladder samples were obtained by taking a biopsy during a TURBT or TURP, prostate samples were taken during TURP and the liver and kidney (pigs) were bought at a supermarket. The bladder and prostate samples were snap frozen in liquid nitrogen and stored in an -80°C freezer until required for experimentation. The liver and kidney tissue were used fresh. The constituent samples were bought from Sigma – Aldrich. Multivariate and least squares analysis were used to ascertain the biochemical basis of the differing pathologies within the bladder and the prostate gland, as well as to test diagnostic algorithms produced by a colleague in our group. Depth profiling through the bladder and prostate gland was shown to be feasible by utilizing the Kerr gating technique as was the suppression of fluorescence from dark tissue (liver and kidney). We have shown for the first time, that we can utilise Raman spectroscopy to determine the biochemical basis of pathologies of the bladder and the prostate gland. With the help of the Kerr gating technique we also obtained spectra from different depths through them. We also suppressed fluorescence and resonantly enhanced Raman spectra from dark tissue. These have major implications in terms of understanding pathogenesis and disease progression and also the potential to accurately assess depth of tumour invasion.